2019
DOI: 10.1111/jmft.12405
|View full text |Cite
|
Sign up to set email alerts
|

An International Examination of the Effectiveness of Functional Family Therapy (FFT) in a Danish Community Sample

Abstract: Youth behavior problems have increased in prevalence in Scandinavian countries. Functional Family Therapy (FFT) has been shown to be an effective intervention across diverse populations and international contexts. The current study examines the effectiveness of FFT within a Danish-community sample in a pre-post comparison design and includes 687 families. Observed outcomes included both parent-and/or youth-reported domains of youth behavior, family dysfunction, school attendance and performance, and substance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
10

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 47 publications
1
9
0
10
Order By: Relevance
“…Although the ANOVA analyses found no improvements in either group, RCIs and clinical recovery rates revealed that a greater proportion of youth in the FFT group reported better family functioning at Time 2 relative to Time 1. In comparison, earlier evaluations generally reported improvements in family functioning (Hartnett et al, 2016;Vardanian et al, 2019). However, it is noteworthy that a recent UK-based RCT also did not find greater improvements on indicators associated with family functioning (Humayun et al, 2017).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Although the ANOVA analyses found no improvements in either group, RCIs and clinical recovery rates revealed that a greater proportion of youth in the FFT group reported better family functioning at Time 2 relative to Time 1. In comparison, earlier evaluations generally reported improvements in family functioning (Hartnett et al, 2016;Vardanian et al, 2019). However, it is noteworthy that a recent UK-based RCT also did not find greater improvements on indicators associated with family functioning (Humayun et al, 2017).…”
Section: Discussionmentioning
confidence: 76%
“…This could be due differences in the psychometric measures employed. Furthermore, previous evaluations have found effect sizes of parent‐reported outcomes to be generally higher than youth‐reported outcomes (Vardanian et al., 2019 ). RCIs and clinical recovery rates yielded convergent findings in partial support of FFT’s effectiveness in relation to well‐being.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Kemudian dalam perkembangan intervensi ini, sejumlah ulasan telah mengidentifikasi FFT sebagai salah satu program intervensi berbasis bukti yang muncul untuk remaja-remaja berisiko tinggi dan keluarga mereka (Sexton & Turner, 2010). Setelah itu, sejumlah penelitian terbaru telah menilai portabilitas FFT di negara-negara Eropa, termasuk Irlandia, Inggris, Skotlandia, Norwegia, dan Denmark, serta di negara Asia (Vardanian et al, 2020). Namun demikian, berdasarkan hasil penelitian yang dilakukan oleh Weisman dan Montgomery (2019), dengan metode multicabang yang berdasarkan pada 15 database, 10 situs web, dan kontak ahli, menerangkan bahwa kualitas ulasan penelitian tentang FFT secara keseluruhan rendah, sehingga penelitian tentang FFT masih membutuhkan penyelidikan yang lebih ketat.…”
Section: Pengantarunclassified
“…Selain itu, beberapa penelitian setelahnya menunjukkan bahwa FFT telah terbukti efektif dalam menurunkan perilaku bermasalah dan tingkat residivis pada remaja di berbagai konteks negara. Sejumlah penelitian telah menilai portabilitas FFT di negara-negara Amerika, Eropa, (termasuk Irlandia, Inggris, Skotlandia, dan Denmark) dan Asia (Graham et al, 2013;Hartnett et al, 2015;Marshall et al, 2016;Vardanian et al, 2020). Di negara Asia diwakili oleh penelitian Gan et al (2018) dalam konteks Singapura.…”
Section: Penilaian Kualitas Penelitianunclassified